2022
DOI: 10.47368/ejhc.2022.205
|View full text |Cite
|
Sign up to set email alerts
|

Deprived, Radical, Alternatively Informed

Abstract: The Covid-19 pandemic was accompanied by a massive increase of the supply and demand for pandemic-related information. Similarly, conspiracy theories about the origins and functions of the Covid-19 virus flourished during the early stages of the pandemic. The present study draws on a nationally representative sample of the German population aged 18+ (N = 1,207) to investigate factors that are associated with people’s susceptibility to believe in such theories. We draw on research from sociology, political scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…According to the existential threat model (Van Prooijen, 2019), uncertainty and fears are a precondition for susceptibility to conspiracy theories. In line with this argumentation, several studies found positive relationships between economic threats and belief in pseudoscientific information or conspiracy theories ( Čavojová et al, 2022;Ziegele et al, 2022), information usually spread on alternative media (Boberg et al, 2020). A recent study found that the relationship between perceived or actual poor economic country and the development of conspiracy theories about elites ruling their nation is found across 36 countries (Hornsey et al, 2023).…”
Section: Fears and Media Consumptionmentioning
confidence: 78%
See 2 more Smart Citations
“…According to the existential threat model (Van Prooijen, 2019), uncertainty and fears are a precondition for susceptibility to conspiracy theories. In line with this argumentation, several studies found positive relationships between economic threats and belief in pseudoscientific information or conspiracy theories ( Čavojová et al, 2022;Ziegele et al, 2022), information usually spread on alternative media (Boberg et al, 2020). A recent study found that the relationship between perceived or actual poor economic country and the development of conspiracy theories about elites ruling their nation is found across 36 countries (Hornsey et al, 2023).…”
Section: Fears and Media Consumptionmentioning
confidence: 78%
“…Bendau et al (2021) report a positive correlation between health-related fears and vaccination intention, but a negative correlation with the item focusing on economic threats. Ziegele et al (2022) found in their German sample also a negative relationship between economic deprivation and vaccination intentions. We therefore predict: H3: Fears focused on health threats correlate positively with vaccination acceptance.…”
Section: Fears and Vaccination Acceptancementioning
confidence: 88%
See 1 more Smart Citation
“…At the same time, it is well known that there are important psychological processes underlying people's tendency to believe in conspiracies. The sense of relative deprivation, which is a perception of being socially or financially disadvantaged compared to other people, and in comparison with one's own past situation, is clearly one of them (Bilewicz & Krzemiński, 2010; Hornsey et al., 2023; Ziegele et al., 2022). In this article, we propose that, apart from a direct transmission of conspiracy theories through social media, the extensive passive consumption of such media could increase people's sense of deprivation compared to other people who are presenting their successful narratives through such media.…”
Section: Passive Social Media Use Positively Predicts Beliefs In Cons...mentioning
confidence: 99%
“…In this case, too, the assessment of their past economic situation as better than their current and future one was found to be a significant antecedent of conspiracy beliefs (Hornsey, et al, 2023). Recent studies showed that relative deprivation not only breeds conspiracy theories about COVID‐19 but it also affects people's willingness to vaccinate (Ziegele, et al., 2022), therefore deprivation could be viewed as an important obstacle to public health. Following from these expected effects of personal relative deprivation on conspiracy beliefs and taking into account the role that passive social media use is expected to play in triggering beliefs in conspiracy theories, we formulated the following prediction: …”
Section: Social Media Use Leading To Conspiracy Beliefs Via Personal ...mentioning
confidence: 99%